Alveolar Macrophages Contribute to Respiratory Tolerance by Inducing FoxP3 Expression in Naive T Cells - MILLS, KINGSTON; KEANE, JOSEPH; RUANE, DARREN; COLEMAN, MICHELLE; MORAN, BARRY (My University, 2013)
Alveolar macrophages (AMs) from mice and humans have long been known to contribute to maintaining tolerance in the lung. Studies have shown that AMs can induce anergy in CD4+ T cells. Nitric oxide, prostaglandins, and leukotrienes have been implicated in AM-mediated tolerance. However, it remains unclear what effect, if any, AMs exert on FoxP3 induction in CD4+ T cells from mice and humans, and whether or not other immunomodulators might play a role. AMs were isolated from bronchoalveolar lavage (BAL) fluid from either mice or humans, and cocultured with enriched naive CD4+FoxP3− T cells. We show here for the first time that AMs and AM-conditioned media (AM-CM) from mice and humans induced FoxP3 expression in naive CD4+ T cells in vitro, an outcome that was reversed in part either by inhibiting retinoic acid (RA) binding to its receptor (RAR), or by blocking transforming growth factor (TGF)–β1 signaling. A nasal administration of the RAR antagonist reduced the frequencies of CD4+FoxP3+ T cells in the lungs of mice after aerosol challenge with Bordetella pertussis. In addition, we found that the intranasal vaccination of mice with ovalbumin (OVA) protein in conjunction with an RAR inhibitor led to a significant increase in OVA-specific serum IgE. Our findings suggest that AMs can mediate tolerance in the lungs of mice and humans via RA and TGF-β1. These data may have implications in the development of nasal vaccines in the future.
PUBLISHED
Keywords: retinoic acid; TGF-β1; FoxP3; alveolar macrophages; Immunology, Inflammation & Infection